Does managerial ability influence the quality of financial reporting?. Issue 4 (August 2018) - García-Meca, Emma; García-Sánchez, Isabel-María
Abstract: The purpose of this paper is to study the influence of managerial ability on the quality of their financial reporting. Using a large bank sample from nine different countries and for the time period 2004–2010, we expect that bank earnings quality and accounting conservatism increase with more able managers that disclose more accurate earnings and who report higher information about banks' future earnings and cash flows. The results confirm that managerial abilities play a significant role in the quality of financial reporting in banks, and that capable bank managers are less likely to manage earnings opportunistically. This study is timely and relevant given the recent emphasis on earnings quality of banks over the last few years, and the criticisms of managerial abilities after the financial crisis. The evidence from this study can help standard-setters and regulators to better understand the business practices and accounting behavior of banks in the light of managerial abilities.